Challenging The City Scale. Graz (2018)
“We started being interested in this area in 2014,” says Anke Strittmatter, a German urbanist who teaches at FH Joanneum and leads the Human Cities Graz team. “We looked at everything we could: the colours of the facades, the lighting, the history of the houses and the communities that live here.” Although it is close to the city centre, Jakomini Street and its surroundings are considered a run-down area. Some of the shops are closed and some of the buildings are empty. Moreover, the poor quality of the public space is a concern. “The street is very narrow and there are two tram lines passing through,” Anke Strittmatter says. “As a result, there’s nowhere to sit or stand and people just walk along as quickly as they can.” How can this transit space be transformed into a shared space where people can meet and spend time without being forced to consume? This is the question FH Joanneum decided to explore as its Human Cities experiment. To begin with, students of Information and Exhibition Design carried out a community survey and observed the public space. They used research methods developed by Danish architect and urban designer Jan Gehl, such as counting, mapping and tracing. As a result, “the students concluded that people wanted somewhere to sit and more greenery,”says Erika Thümmel, who has a special interest in the street. As well as being a teacher of Exhibition Design at FH Joanneum and a member of the Human Cities team, she lives in Jakomini Street and has been an activist ever since she moved here nine years ago.